Effect of teacher's competencies on student academic performance in spm exam mediated by holistic centered learning at sumur religious secondary school in terengganu - Nordiana, Mohd Nor; Juliana, Mohd Nor; Rahimah, Embong; Habsah, Muda (2016)
Education recent review mostly about creating 21st-century learning environments therefore new classroom approach for Malaysian students which implemented clarity and understanding, with engage teachers and students in new ways should be studied. Students are an important asset for the future of the country that need to be addressed, cared for, guided, appreciated its existence, loved every moment and can develop their potential according to sunnah and moral values. In this concept paper it determines the factors that contribute to excellent result achievement in Terengganu state that contribute to National GPA 1n SPM 2015. Terengganu state record excellence SPM GPA grades better than National GPA grades for almost more a decade. The study employed a mix method using quantitative, involving survey semi-questionnaires instrument for teachers from chosen excellent religious secondary school under BPI ( Bahag1an Pend1d1kan Islam, KPM) that undergo Student Ultimate Personality Programs (SUMUR) and qualitative in form of Interview for Sic+, PPD excellent guide teacher for the excellent chosen SABK and SMKA secondary school (School Improvement Specialist Coaches (SISC+) under the Malaysian Education Blueprint, PPPM 2013-2025.). The independence variable on teacher competencies. the mediator on holistic centered-learning and dependent variable on student academic performance (based on SPM 2015 result) will be specified in each instruments. The finding will help 1n many different ways most importantly to KPM, BPI School administration . teacher , student and entire education system as key factor for better end product in facing 21'1 century globalization.